ANALISIS PENILAIAN BANGUNAN RUMAH TINGGAL DI KOTA DENPASAR - Rijasa, M. Mariada; Sukrawa, M.; Nadiasa, Mayun (JURNAL SPEKTRAN, 2014)
Research on factors that affect the value of residential buildings in the city of Denpasar has been done consisting of literature review, interviews with experts, data collection and statistical analysis. Obtained from literature review were 45 factors which then grouped into four, namely: land characteristics, environment, location, and building characteristics. Survey on 27 valuation expert respondents was done to obtain their perceptions on the factors, and then their perceptions were measured with Likert scale. The data were then statistically tested to determine its validity and reliability, after which factor analysis was performed to obtain factors that truly valid within its group. To further evaluate the dominant factor in each group, two hundred data of previously assessed residential buildings were collected and analyzed using multiple linear regression. Results showed that group of factors that affect the value of residential building the most is location (7.723) followed by environment (3.843), building characteristics (3,741) and land characteristics (3.253). Downtown area, road width, building area, and land area are the factor of location, environment, building characteristics, and land characteristics, respectively, that dominantly showed positive effect within its group. SUTET transmission, poor road conditions, poor physical condition of the house, and the land at road end "tusuk sate" dominantly showed negative impact within its group.
Keywords: valuation, residential buildings, factor, factor analysis, regression